2022
DOI: 10.3390/jcm11113179
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Arterial Stiffness in Patients with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: Population-based studies have suggested that patients with inflammatory bowel disease (IBD) might be at an increased risk for cardiovascular diseases. A meta-analysis was performed on clinical studies to evaluate endothelial function, arterial stiffness, and carotid intima-media thickness (cIMT) in patients with IBD, after searching PubMed, Embase, Cochrane library, and Web of Science databases. A random-effects model was used to allow for the pooling of studies and for determination of the overall effect. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
2
7
0
Order By: Relevance
“…Studies have demonstrated that endothelial cell dysfunction, as reflected by decreases in flow-mediated dilatation and pulse arterial tonometry indices, is present in patients with IBD [ 8 , 9 ]. Consistent with this, our recent meta-analysis showed that patients with IBD were significantly associated with endothelial cell dysfunction, increased arterial stiffness, and carotid intima-media thickness [ 10 ].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Studies have demonstrated that endothelial cell dysfunction, as reflected by decreases in flow-mediated dilatation and pulse arterial tonometry indices, is present in patients with IBD [ 8 , 9 ]. Consistent with this, our recent meta-analysis showed that patients with IBD were significantly associated with endothelial cell dysfunction, increased arterial stiffness, and carotid intima-media thickness [ 10 ].…”
Section: Introductionsupporting
confidence: 65%
“…Chronic inflammation has been known to be associated with endothelial dysfunction [ 33 ]. Our recent meta-analysis demonstrated that patients with IBD were significantly associated with endothelial cell dysfunction, increased arterial stiffness, and carotid intima-media thickness [ 10 ]. In the present study, we observed that plasma TNF-α, IL-6, and IL-17 were significantly increased in mice with colitis.…”
Section: Discussionmentioning
confidence: 99%
“…25 All these factors were strong predictors of future cardiovascular accidents, including coronary accidents and CVAs. 25,26 These results indicated that IBD patients might have a higher risk of developing CVA than the general population. However, the results of previous metaanalyses were controversial.…”
Section: Discussionmentioning
confidence: 98%
“…A meta‐analysis of 41 studies showed that patients with IBD exhibit significant endothelial dysfunction, increased arterial stiffness, and carotid intima‐media thickness 25 . All these factors were strong predictors of future cardiovascular accidents, including coronary accidents and CVAs 25,26 . These results indicated that IBD patients might have a higher risk of developing CVA than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported different physiological and pathophysiological conditions associated with increased arterial stiffness [ 1 ]. For instance, it has been shown that arterial stiffness is increased not only in atherosclerotic cardiovascular disease but also in systemic sclerosis, in autoimmune diseases characterized by endothelial dysfunction and fibrosis of skin and visceral organs [ 2 ], in inflammatory bowel disease which is accompanied with endothelial dysfunction [ 3 ] as well as in subclinical and overt hypothyroidism, hyperthyroidism and in primary hyperparathyroidism. It seems that levothyroxine replacement therapy causes an improvement in arterial stiffness in patients with hypothyroidism and that arterial stiffening is reversed by parathyroidectomy in primary hyperparathyroidism [ 4 ].…”
mentioning
confidence: 99%